THE RELATIONSHIP BETWEEN CUSTOMER SATISFACTION AND SECURITY TOWARD TRUST AND ITS IMPACT ON REPURCHASE INTENTION (SURVEY ON CUSTOMER OF ELEVENIA ONLINE WEBSITE) - Rizan, Mohammad; Bakar, Kemal Abu; Saidani, Basrah (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2015)
The purpose of this research are to: examine empirically the effect of customer satisfaction to trust on customer, the impact of security to trust on customer, the impact of the customer satisfaction to repurchase intention on customer, the effect of security to repurchase intention on customer, the effect of trust to repurchase intention on customer, the effect of customer satisfaction to repurchase intention through trust as intervening variable on customer, the effect of security to repurchase intention through trust as intervening variable on customer of Elevenia website online. This research used survey methods for collecting data. The object of this research is 200 respondents who had purchased in Elevenia website online for a period of one year backward. This research used SPSS software version 22 and SEM (Structural Equation Modeling) LISREL version 8.7 for data analysis. Hypothesis testing showed that: the customer satisfaction has a positive effect and significance on trust, the security has a positive effect and significance on trust, the customer satisfaction has a positive effect and significance on repurchase intention, the security has a positive effect and significance on repurchase intention, the customer satisfaction has a positive effect and significance on repurchase intention through trust as intervening variable and the security has a positive effect and significance on repurchase intention through trust as intervening variable. Keywords: Customer Satisfaction, Security, Trust, Repurchase Intention.